Osteodystrophy in the millennium - Ritz, Eberhard; Schömig, Michael; Bommer, Jürgen (Kidney international, 1999)
Despite three decades of intensive research on the derangements of calcium phosphate metabolism of renal failure, several unresolved issues are still with us at the turn of the millennium: poor control of hyperphosphatemia, relative inefficacy of active vitamin D to prevent progressive parathyroid hyperplasia, and persistence of bone disease despite lowering of parathyroid hormone (PTH) and administration of active vitamin D. Although predictions are problematic, it is not unreasonable to hope that, barring unforeseen side effects, calcimimetics will prove to be valuable for suppressing or even preventing hyperparathyroidism, thus potentially replacing, at least in part, active vitamin D. There is also reason to hope that more effective phosphate binders with fewer side effects will become available and that controlled studies will provide a rationale for the administration of estrogens to dialyzed women. As regards understanding the pathological mechanisms, one can anticipate that the disturbances leading to autonomous growth of parathyroid cells will be elucidated and the signals involved in osteoclast/osteoblast differentiation pathways and osteoclast/osteoblast coupling will be clarified, with obvious impact on patient management.